A case study on the superior-subordinate relationships in the U.P. Cherubim and Seraphim and the U.P. Concert Chorus. - Rivera, Robin Daniel Zarco 1958- (1980.)
A case study was made on the U.P. Cherubim and Seraphim and U.P. Concert Chorus to determine how superior-subordinate relationships affect the performance of such groups. As a staff member of the Cherubim and Seraphim and having worked with the Concert Chorus on several occasions, the researcher has a basic knowledge of the organization structures as well as working relationships existing within the two groups. Augmenting this basic knowledge with research-based methods such as the use of questionnaires and personal interviews, the researchers learned of the representative views as well as perceptions of a set-up for conductors and members aliked
Thesis (Bachelor of Arts)--University of the Philippines Diliman.
Vita.
Typescript.
Keywords: University of the Philippines Cherubim and Seraphim; University of the Philippines Concert Chorus; Choirs (Music).